PEMBERDAYAAN IBU-IBU KADER SURABAYA HEBAT DALAM BUDIDAYA DAN PENGELOLAHAN TOGA - Ristani Widya Inti; Dwie Retna Suryaningsih; Diah Tri Hermawati; Endang Siswati; Jajuk Herawati; Fahmi Romadhani Winarto (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2023)
Community empowerment is a process to strengthen community independence in overcoming the problems faced. The Surabaya City Government, through the health Office, has initiated socialization activities and assistance in the use of Family Medicinal Plants (TOGA) in accordance with the regulation of the Minister of Health No. 9 of 2016. This program aims to educate the public about the benefits of using TOGA in overcoming minor health problems. In order to achieve this goal, the mothers of Surabaya Hebat cadres in Lidah Kulon play an important role by providing training and counseling on TOGA cultivation and processing. Participatory approach is used in mentoring methods, which involve the community actively in the planning and implementation of activities. The results of this activity include increasing public knowledge about TOGA, economic empowerment through processing TOGA products, and preservation of traditional knowledge. The success of this program is indicated by the improvement of people's quality of life, environmental awareness, and economic independence in the context of the use of medicinal plants. Thus, community service by Surabaya Hebat cadres in Lidah Kulon in TOGA cultivation and processing has succeeded in creating a positive impact in various aspects of local people's lives.